Socio-economic risk assessment of flooding for Russian coastal regions - Stepan Zemtsov; Vera Kidyaeva; Maxim Fadeev (European Regional Science Association (ERSA), 2013)
An increasing number of hazardous natural phenomena is one of the results of climate change for Russia. Risks increase in coastal areas with high concentration of hazards and high density of population and economic activity. In 2012, an integrated damage from floods was about 1 billion euros; floods had caused death of over 200 people. Particularly destructive consequences were for Krymsk in Krasnodar region. The purpose of the work is to estimate the influence of hazardous hydrological phenomena (e.g. floods, underflooding and surges) on sustainable development of coastal regions. The first stage was to estimate potential damage for population and economy of Kaliningrad and Leningrad regions (the Baltic Sea coastal zone). The authors used methodology of EMERCOM based on the model of direct (loss of life, destruction of buildings, etc.) and indirect effects (loss of profits, loss of the budget, etc.). A database of chosen indicators based on satellite images, maps, statistical yearbooks and reports of entities, was prepared. Maximum direct potential damage for both regions in 2012 was about 15.7 billion euros, but indirect damage was more than 25.5 billion euros. The damage increased with growth of economic activities without proper strengthening of protective infrastructure. Vulnerability assessment for municipal societies of Krasnodar Region (the Azov and the Black Sea coastal zone) was the second stage. A database, as a matrix of 250 parameters from 2005 to 2010 for 14 municipalities, was developed. The parameters were divided into several blocks according to UNU-EHS methodology: ?exposure? and ?vulnerability?, consisting of ?susceptibility?, ?coping capacity? and ?adaptive capacity?. Relevant indicators were selected, verified by statistical methods, and sub-indices were calculated. Areas with the highest risks are Slavyansk, Krymsk, Krasnoarmeysk and Temryuk municipal districts. Olympic Sochi has one of the lowest risks, but it is increasing. Both approaches were integrated using ?field? data (opinion polls, interviews, municipal statistics, etc.). The study was conducted in Slavyansk district, in the Kuban river delta (1-5 m. above sea level). Environmental, economic and social risks with a set of damages were identified. Integrated risk was calculated using GIS and developed formulas: R = Σpj*Dj, where R ? risk, p ? probability, D ? expected damage, j ? flood zone, and Dj = ΣdIi * Vij * Sj, - C, where dI ? potential damages per unit of area, V ? vulnerability, S - area, I - type of risk, i - type of damage, C - costs of preventive measures. The risk is growing and covers new areas. In Russia, probability growth of hazardous natural events (caused by climate change) coincides with increasing risk of technogenic catastrophes because of errors in planning and underinvestment in protection systems. Sustainable development is limited by these factors.
Keywords: 330; Risk assessment; Russian coastal zone; hazard of flooding; vulnerability; damage evaluation